2010
DOI: 10.1007/s10389-010-0366-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk factors of HCV infection among hemodialysis patients in countries of the Eastern Mediterranean Regional Office of WHO (EMRO): a quantitative review of literature

Abstract: Background Hepatitis C virus infection (HCV) is the major co-morbidity of patients on chronic hemodialysis. There are many scattered and heterogeneous data about this infection in hemodialysis patients living in countries of the Eastern Mediterranean Region Office of WHO (EMRO) and its distribution is unknown in this region. Aims To provide a more comprehensive tabulation of available data on the epidemiological characteristics and risk factors for HCV infection in hemodialysis patients in Iran and other EMRO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 56 publications
2
59
1
Order By: Relevance
“…The seroepidemiology of HCV infection among beta-thalassemia patients has been estimated at 18%, 45%, 63%, and 69% in Iran, Pakistan, Saudi Arabia, and Egypt, respectively. Among Iranian beta-thalassemia patients, splenectomy, high frequency of blood transfusion, advanced age, and transfusion before 1996 were risk factors for HCV infection (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seroepidemiology of HCV infection among beta-thalassemia patients has been estimated at 18%, 45%, 63%, and 69% in Iran, Pakistan, Saudi Arabia, and Egypt, respectively. Among Iranian beta-thalassemia patients, splenectomy, high frequency of blood transfusion, advanced age, and transfusion before 1996 were risk factors for HCV infection (8).…”
Section: Introductionmentioning
confidence: 99%
“…Although the prevalence of HCV infection has been decreasing in recent years among Iranian blood donors due to blood supply tests (1), the frequency of HCV subtypes differs among HCV patients in various provinces of Iran and fluctuates with time (7). The prevalence of HCV is much higher among high-risk groups, such as beta-thalassemia patients (8).…”
Section: Introductionmentioning
confidence: 99%
“…Positive ELISA results were confirmed by the RIBA test in 568 cases, and the highest and lowest prevalence rates were seen in Semnan (32%) and Zanjan (2%), respectively. The rate of HCV infection in thalassemia patients from Pakistan, Saudi Arabia and Egypt was 45, 63 and 69%, respectively [51]. Lower prevalence rate in Iran compared to these countries could be due to the screening systems for blood transfusion in Iran.…”
Section: Prevalence Of Hcv Among Thalassemia Patientsmentioning
confidence: 98%
“…Another study by Oza et al on 193 children with thalassemia major reported the prevalence of HCV infection as 7.8% [50]. In a systematic review by Alavian et al in Iran [51], of 5229 patients with thalassemia, 941 (17.9%) were anti-HCV antibodypositive. Positive ELISA results were confirmed by the RIBA test in 568 cases, and the highest and lowest prevalence rates were seen in Semnan (32%) and Zanjan (2%), respectively.…”
Section: Prevalence Of Hcv Among Thalassemia Patientsmentioning
confidence: 99%
“…Currently, approximately 170 million people are infected with HCV (2,5). Injecting drug use is the most common route of transmission, thus IDUs have the highest prevalence of HCV infection and also constitute a potential reservoir of HCV in the community (6)(7)(8).…”
mentioning
confidence: 99%